Smartphone Sensor-Based Physics Module for Hands-On Learning in Waves and Optics - Endra Putra Raharja; Edi Sutomo; Febrian Andi Hidayat; Asih Kasan; Nia Mangkasa (Jurnal Penelitian Pendidikan IPA, 2025)
The limited laboratory equipment in many schools hinders students in conducting physics experiments, so that learning is more theoretical and less supportive of practice-based understanding. This study aims to develop a smartphone sensor-based physics experiment module on wave and optical materials that is valid, practical, and effective, and allows students to conduct experiments flexibly and independently. This research uses the Research and Development (R & D) method with the Borg & Gall model. Validation by media and material experts showed that this module has met the eligibility standards, with a score of 3.67 (73.4%) for media aspects and 3.56 (71.2%) for material aspects. The practicality test showed that this module can be used well in experimental learning, with a score of 3.48 (69.6%) in the “Good” category. Evaluation of effectiveness through comparison of pre-test and post-test showed an increase in learning outcomes with an N-gain of 0.55 (medium category). These results indicate that the integration of smartphone sensors in physics experiments can be an alternative solution for schools with limited laboratory facilities. This module offers a more flexible, accessible and technology-based learning approach. Future research can develop similar modules for other physics materials and evaluate their effectiveness in various learning scenarios.